The Implementation of Contraceptive Legalization and its Moral Implications for Muslim Adolescents in Rural Indonesia - Khairunida, Daan Dini; Muharis, Achmad Yan; Fitriani, Rizqi (Sinthop: Media Kajian Pendidikan, Agama, Sosial dan Budaya, 2025)
Population growth remains a critical issue for Indonesia, leading to the government’s implementation of the Family Planning (Keluarga Berencana) program, which promotes contraceptive use to control fertility and improve reproductive health. In rural Muslim communities such as Sukarapih Village, Bekasi, the program encounters moral and cultural resistance shaped by religious interpretation and social norms. This study examines how the government’s contraceptive policy is implemented and morally negotiated within this religiously conservative context, focusing on its influence on adolescent understanding and behavior. Using a qualitative descriptive design, the research was conducted from March to May 2024 through eighteen in-depth interviews and two focus group discussions with religious leaders, midwives, parents, and adolescents. Thematic analysis identified five key patterns: knowledge and misconceptions, religious gatekeeping, service delivery, family supervision, and peer influence. Findings reveal that contraceptive policy implementation operates through moral negotiation among health institutions, families, and religious authorities. While health workers adapt counseling to emphasize health protection, religious leaders and parents maintain control over adolescents’ moral development. Contraceptive access thus functions as both a public health initiative and a moral discourse shaped by community values. The study concludes that policy success depends not only on service provision but also on alignment with religious and ethical frameworks. Culturally sensitive approaches that integrate Islamic moral principles, family engagement, and adolescent education can strengthen both reproductive health outcomes and moral integrity in Muslim-majority rural settings.